Conditions for Loach (Misgurnus fossilis) Embryo Vitrification in Cryoprotective Media - Mikson, K. B.; Kopeika, E. F.; Linnik, T. P. (Problems of Cryobiology and Cryomedicine, 2009)
Resistance of loach (Misgurnus fossilis) embryos to the effect of 5 cryoprotective media was investigated and the conditions of their vitrification were determined. The obtained experimental data demonstrated, that at a developmental stage, corresponding to the heart beating onset, the highest number of vitrified embryos (up to 100%) was observed during 30 min incubation within a cryoprotective medium, consisting of 30% sucrose, 10% ethylene glycol, 3% polyethylene oxide–1500 and 20% 1,2-propane diol. Vitrification temperature of loach embryos at this developmental stage was within –80...–176°C range.